2021
DOI: 10.3390/plants10071277
|View full text |Cite
|
Sign up to set email alerts
|

Uptake Dynamics of Ionic and Elemental Selenium Forms and Their Metabolism in Multiple-Harvested Alfalfa (Medicago sativa L.)

Abstract: A pot experiment, under greenhouse conditions, was carried out aiming at investigating the agronomic biofortification of alfalfa (Medicago sativa L.) with Se and monitoring the Se uptake and accumulation dynamics within four consecutive harvests within the same growing season. Two ionic Se forms, i.e., sodium selenate (Se (VI)) and sodium selenite (Se (IV)), were applied once at a rate of 1, 10, and 50 mg kg−1 (added on Se basis), while 10 and 50 mg L−1 of a red elemental Se (red Se0) were used; all Se treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 52 publications
2
11
0
Order By: Relevance
“…After applying exogenous Se (SeNPs or Na 2 SeO 3 ), the absorption and accumulation of total Se in cowpea pods showed a dose-response relationship. The results were consistent with the research results on other leguminous plants such as Pisum sativum , Astragalus sinicus and Medicago sativa [ 35 , 36 , 37 ]. The results showed that foliar spraying of 37.5–750.0 mg/L Na 2 SeO 3 could effectively increase the contents of macromolecular bound Se and total Se in pea seedlings, which were 8.75–38.75 times and 6.01–55.65 times higher than those in the control, respectively [ 38 ].…”
Section: Discussionsupporting
confidence: 92%
“…After applying exogenous Se (SeNPs or Na 2 SeO 3 ), the absorption and accumulation of total Se in cowpea pods showed a dose-response relationship. The results were consistent with the research results on other leguminous plants such as Pisum sativum , Astragalus sinicus and Medicago sativa [ 35 , 36 , 37 ]. The results showed that foliar spraying of 37.5–750.0 mg/L Na 2 SeO 3 could effectively increase the contents of macromolecular bound Se and total Se in pea seedlings, which were 8.75–38.75 times and 6.01–55.65 times higher than those in the control, respectively [ 38 ].…”
Section: Discussionsupporting
confidence: 92%
“…The crude fat content exhibited no significant differences. Previous studies have found that exogenous selenium influences the protein content or distribution in plants (Kovács et al, 2021). Although selenium is not considered an essential trace element for plants, numerous authors have confirmed its beneficial effect on plant life (Gupta & Gupta, 2017;Malagoli et al, 2015).…”
Section: Pigment Content and Nutrient Compositionmentioning
confidence: 98%
“…5 Alfalfa being a good model plant has a bright future of Se enrichment in green biorefining. 6 The process of Se enrichment in plants is affected by ways of Se application, the forms of Se, and the contents of Se application. 7 Different forms of exogenous Se can be selected according to different parts of Se biofortification plants.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, in the Se fortification of alfalfa, the addition of Se promoted the yield and increased the Se content to 40 mg kg −1 5 . Alfalfa being a good model plant has a bright future of Se enrichment in green biorefining 6 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation